The impact of postpartum depression symptom on breastfeeding outcomes: a literature review - Shafi’ah, Shafi’ah; Indrani, Rahma Sasmita; Shabira, Aghniyya; Adnani, Qorinah Estiningtyas Sakilah; Susiarno, Hadi; Adepoju, Victor Abiola (Media Penelitian dan Pengembangan Kesehatan, 2026)
Background: Postpartum depression is among the most prevalent mental health conditions during the postpartum period. Postpartum depression is regarded as detrimental to breastfeeding. Depressed mothers may experience a diminished interest and attraction towards their infants. Ultimately, the mother is incapable of adequately caring for her infant, including the inability to breastfeed directly. Objective: Consequently, we performed a literature analysis to rigorously assess the evidence regarding the correlation between postpartum depressive symptoms and breastfeeding habits. Methods: A literature review utilized the PubMed, Scopus, and Science Direct databases, referencing selected publications published between 2019 and 2024. A total of 9,146 articles were obtained from the specified databases and subsequently analyzed using the PRISMA. Results: The review of 22 selected articles revealed a strong correlation between postpartum depression symptoms and decreased breastfeeding success. Depressed mothers tend to have lower breastfeeding initiation rates. In addition, other factors influence breastfeeding success, such as the benefits of breastfeeding, societal and ecological assistance, malnutrition, insomnia, social and demographic characteristics, psychological factors, and patterns of breastfeeding. Conclusion: Postpartum depression symptoms correlate with breastfeeding success. Health practitioners should implement mental health evaluation in breastfeeding programs to identify maternal risk, which can be treated early. This enhances the rates of successful breastfeeding practices and supports the mother's and child's health.